Socioeconomic determinants and inequalities in exclusive breastfeeding among children in Peru - Hernández-Vásquez, Akram; Vargas-Fernández, Rodrigo (Frontiers in Nutrition, 2022)
Introduction Although Latin America and the Caribbean have one of the highest prevalences of exclusive breastfeeding (EBF), the countries in this region have socioeconomic determinants that influence the frequency of this practice and do not allow achieving the 70% target recommended by the World Health Organization. Therefore, the objective of the study was to examine the socioeconomic determinants and perform a decomposition analysis of socioeconomic inequalities in EBF in Peruvian children 6 to 59 months of age. Methods A cross-sectional study was carried out using the 2021 Demographic and Family Health Survey. The dependent variable for the study was EBF up to 6 months of age and the wealth index variable was used to perform the inequality analysis. Poisson log generalized linear regression models were fitted to evaluate the association between EBF and the independent variables, and concentration curves and Erreygers concentration index decomposition were used to analyze inequalities in EBF. Results A total of 9926 surveyed participants were included. The prevalence of EBF was 70.5% (95% confidence interval: 69.2-71.8). Women who were married, self-identified as native, received EBF training, resided in the highlands and jungle, and their child was the second or older showed a higher likelihood of EBF. In the inequality analysis, EBF was concentrated among the poorest mothers and the major contributors were residing in the highlands and jungle and belonging to the middle and wealthy quintiles. Discussion Our findings suggest that the main strategies to encourage the practice of EBF should be focused on all mothers regardless of their socioeconomic status in order to reduce the EBF gap between richer and poorer women.